Reversibility and chiasm: false equivalents? An alternative approach to understanding difference in Merleau-Ponty's late philosophy. Issue 2 (4th March 2017) - Hughes, Fiona
ABSTRACT: The chiasm is usually considered the key notion for Merleau-Ponty's later philosophy. I argue against a common conclusion, namely that 'the chiasm' is equivalent to 'reversibility'. Even when the two terms are not taken as interchangeable, the precise nature of their relation has not been adequately established. Focusing exclusively on 'reversibility' has implications for a range of philosophical issues, including relations between self and other. The danger of substituting one term for the other is that existential relations are construed as inversions, rather than as genuine exchanges. I examine two trajectories that can be discovered in 'The Intertwining—The Chiasm'. The first is the inclusion of difference within a peculiar, extended sense of 'reversibility'. The second is the development of a plurality of expressions, among which 'reversibility' is necessary but not sufficient. I go on to argue that Merleau-Ponty secures difference within the chiasm by supplementing the notion of reversibility with 'imminence', the idea that something has not yet occurred. I also propose that the figure of a threshold illuminates how the chiasm operates as a transition where both joining and differentiation occur.